اللجوء الإنساني بين الإتفاقيات الدولية وقواعد الضبط الإداري في الدولة - شيماء كحلوش; سهام يعلاوي (My University, 2018)
Summary: This study addresses one of the biggest issues of concern to the international community and international relations humanitarian crisis, which is the issue of humanitarian asylum, The situation of refugees has changed dramatically since the establishment of UNHCR and its Additional Protocol of 1967, with humanitarian refugees having a legal framework that protects them called international refugee law. rights and guarantees that the host State has a duty to respect, But this protection is limited to that State's right to maintain its public order if it is actually threatened. s international obligations to protect refugees humanely, on the one hand, In compliance with its national obligations, it maintains its public order and security by applying administrative control rules. ................... ملخص : تعالج هذه الدراسة واحدة من أكبر القضايا التي باتت محل إهتمام المجتمع الدولي والعلاقات الدولية ، خاصة بعد ما خلفته الحروب والنزاعات التي إجتاحت العالم من أزمة إنسانية كبرى وهي قضية اللجوء الإنساني، التي توالت المحاولات في وضع حلول لها، ليتغير وضع اللاجئين بشكل جذري منذ إنشاء المفوضية السامية لشؤون اللاجئين وبروتوكولها الإضافي لسنة 1967، حيث أصبح للاجئين إنسانيا إطار قانوني يحميهم يسمى بالقانون الدولي للاجئين، حيث منح لهم حقوق وضمانات تقع على الدولة المضيفة واجب إحترامها، ولكن تجد هذه الحماية حدها في حق تلك الدولة في الحفاظ على نظامها العام إذا تم تهديده فعليا، لتبرز العلاقة هنا بين القانون الدولي والقانون الداخلي في أن اوفق الدولة بين إلتزاماتها الدولية بحماية اللاجئين إنسانيا من جهة، وفي التقيد بواجباتها الوطنية بحفاظها على نظامها وأمنها العام بتطبيق قواعد الضبط الإداري من جهة أخرى. ................... Résumé : Cette étude aborde l’une des plus grandes questions de préoccupation pour la communauté internationale et les relations internationales de crise humanitaire, qui est la question de l’asile humanitaire, La situation des réfugiés a radicalement changé depuis la création du HCR et de son Protocole additionnel de 1967, les réfugiés humanitaires ayant un cadre juridique qui les protège, appelé droit international des réfugiés. Mais cette protection est limitée au droit de cet État de maintenir son ordre public s’il est réellement menacé. Dans le respect de ses obligations nationales, elle maintient son ordre public et sa sécurité en appliquant des règles de contrôle administratif.